Mierniki niefinansowe wykorzystywane do pomiaru działalności ośrodków odpowiedzialności w przedsiębiorstwach krajowych (w świetle badań ankietowych) - Makowska, Ewa (Non-Financial Measures Used by Domestic Enterprises to Evaluate the Performance of the Responsibility Centres (Based on Survey Research), 2005)
The main objective of this paper is the presentation of non-financial measures that are used to determine the performance of responsibility centres. The evaluation of responsibility centres' performance is most often based on financial measures, derived from the cost, income and profit levels. In the literature, the suitability of using non-financial measures, apart from financial ones, to assess the performance of the responsibility centres is often emphasized. Selected results of the survey research are presented in this paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 251-259